Smart solar panels for roadworks / Khairiel Izzat Azman and Normila Ahmad - Azman, Khairiel Izzat; Ahmad, Normila (2023)
Demands for electricity in Malaysia are expected to rise between five to six per cent for the next two to three years in line with increasing urbanisation and rapid industrialisation in the country. Malaysia is currently having a critical energy consumption in the electricity sector, with an additional increase of 4,780-megawatt (MW) capacity. The use of solar panels at buildings has the potential to save electricity and make a green environment. However, poorly performing solar panels at buildings have a negative impact on solar heat gain and sunlight penetration. Therefore, the study proposes the implementation of solar panels for roadworks is the best idea because roads are open space areas and have the potential to consume more solar radiation that can produce more energy for the users. In order to develop Smart Solar Panels for Roadworks to replace all current petroleum-based asphalt roads in Malaysia, the mean annual sun irradiation and the properties of the solar glass were studied. Analyses were carried out qualitatively, using a simulation and a review of literature.